Self-Combustion Synthesis and Ion Diffusion Performance of NaV6O15 Nanoplates as Cathode Materials for Sodium-Ion Batteries. Issue 4 (4th February 2015) - Jiang, Danlu; Wang, Hui; Li, Guopeng; Li, Guangqiang; Lan, Xinzheng; Abib, Mukerem Helil; Zhang, Zhongping; Jiang, Yang
Abstract : NaV6 O15 nanoplates are successfully prepared by a facile and low-cost self-combustion method, which can be considered as promising cathode materials for high capacity sodium-ion batteries (NIBs). Morphology analysis suggests that the self-combustion method leads to the NaV6 O15 nanoplates possessing uniform size, with an average length of 400 nm and width of 100 nm. As the cathode materials, the NaV6 O15 nanoplates exhibit a high initial discharge specific capacity of 149.48 mAh g −1 at a current density of 20 mA g −1 and remains 81.99 mAh g −1 after 30 cycles. The volume change is as little as 6.4%, which is demonstrated by the first-principles calculation. To understand the diffusion performance of sodium ion in NaV6 O15 crystalline lattice, the diffusion coefficients of sodium ion are investigated by the electrochemical impedance spectroscopy (EIS) method and the first-principles calculation. The vacancy-hopping diffusion mechanism is proposed based on a quasi-2D energy favorable trajectory, which relieves the sodium ions diffuse along b -axis in NaV6 O15 lattice with desirable activation energy of 0.481 eV.